Progesterone therapy in recurrent miscarriages: Evaluating formulations, Administration routes and timing for future insights - Ayesha Jamal; Ayesha Hanin Shaikh; Husna Irfan Thalib; Shyma Haidar; Sariya Khan; Anwar A. Alghamdi; Aftab Ahmad; Muhammad Afzal; Usman Thattarauthodiyil; Mahwish Iqbal; et al. (International Journal of Medical Toxicology and Legal Medicine, 2024)
Introduction: Miscarriage, an unfortunate outcome of pregnancy, presents significant challenges in reproductive health for individuals and families worldwide. This review highlights the importance of“Progesterone” ahormone vital for the maintenance of pregnancy, in miscarriage.Decreased progesterone levels are associated with increased myometrial contractility, immunologic vulnerability, and endometrial hyperplasia, predisposing individuals to miscarriage and spontaneous abortion. Progesterone supplementation has thus emerged as a promising therapeutic approach to mitigate the risk of miscarriage, yet the optimal formulation, route, and timing of administration remain subjects of ongoing investigation. Methods: In the context of recurrent and threatening miscarriages, this review investigates various progesterone formulations, delivery routes, and timing protocols including safety and effectiveness profiles of different progesterone formulations, namely oral, vaginal, intramuscular, or subcutaneous, in addition to comparing the disparate studies while analyzing the present literature. We examined the significance of timing in the onset and cessation of progesterone throughout pregnancy, considering preventive and therapeutic approaches. Conclusion: This study attempts to offer insights into improving progesterone therapy procedures for people at risk of recurrent and threatening miscarriages through a comprehensive synthesis of the available data,ultimately guiding future research directions and informing evidence-based clinical care.